The Strength Of Evidence Of Deed Made Under Hands Connected With The Authority Of Notary Legalization And Waarmerking Based On Act No. 30 Of 2004 On The Notary Position - Muhammad Dias Saktiawan; Arif Hijrah Saputra; Ngadino Ngadino (Jurnal Akta, 2020)
This study aims to determine the strength of the deed made under hand as evidence in court, and is there a function legalization and Waarmerking the deed made under hand can provide additional strength of evidence in court. Focused on the research objectives, the formulation of the problem is as follows: First, What is the function of the legalization and Waarmerking deed made under hand in evidence during the trial Court? Second, Do deed made under hand on legalization and in Waarmerking by notaries can be canceled by a judge in court?The research method used is the method of juridical-normative approach. Specifications in this research is descriptive analytical. The data collection method used in this research is secondary data in the form of primary legal materials that legislation, secondary law namely literature, scientific papers, and tertiary legal materials namely legal materials that support primary legal materials and secondary law. While the methods of data analysis using qualitative data analysis.The results showed Legalization and Waarmerking function on deed made under the hand give assurance to the judge about the date, signature, identity of the parties to the agreement, thus helping to judge in terms of proof. Deed made under hand on Legalization and in Waarmerking by notary can be canceled by a judge even though the task of the judge in the case only to share the burden of proof to prove, but ex officio judge can not cancel a deed if not requested cancellation. This is because judges are not allowed to decide unsolicited, so as a deed can be canceled if it does not meet the elements of subjective and objective elements.Keywords: Legalization; Deed; Notary.